MIX DESIGN “BASE A” PADA PENINGKATAN JALAN TELANG JAYA-SUMBER MARGA TELANG, KABUPATEN BANYUASIN - Sumiati sumiati sumiati; Mahmuda; Amirudin; Siswa Indra (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Abstract Aggregat foundation A is a pavement layer located between the surface course and the sub-base course, It is a pavement layer that functions to withstand vehicle loads and as a surface layer palcment, therefore the material to be used must be strong and resistant, and must meet the General sfesifications for road construction. Aggregate gradation, aggregate cleanliness, wear, shape dan surface of the aggregate greatly affect the density and bearing capacity of Base A, therefore PT. Sriwijaya Indo Utama, which will carry ot the project on Telang Jaya-Sumber Telang Road, Muara Telang Jaya District- Sumber Marga Telang, Banyuasin Regency, has asked for a “Base A” mix design in the Materials Testing Laboratory of the Sriwijaya State Polytechnic. The results of testing the physical properties and baering capacity (CBR) of “Base A”, meet the General specifications for road construkstion, so that the mix-design of aggregate Base A can be applied in the project. Key word : mix-design, CBR, Base A